(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Although Christian theologians have often reflected on the theme of the image of God in the human being over the centuries, the history of Christianity is marked by episodes and incidents that have proven that human dignity that derives from the image of God is not an easy concept to assimilate. The inter-denominational tensions in Romania in the first two decades after the Revolution, the interethnic tensions in certain areas of the country, the ethnocentric prejudices and the acute problem of migration from the Middle East are just a few recent or current indicators that the universal Church of Christ is still in need of biblical and theological reflection on the subject of human dignity. In this article, I intend to bring to the reader’s attention one of the most relevant New Testament episodes for the aforementioned subject. It’s the episode of the conversion to the Christian faith of the first group of non-Jews – the Roman centurion Cornelius and his family – through the evangelistic undertaking of the apostle Peter, reported in the Acts of the Apostles 10:1–11:18. Through my reflection on this passage I will seek first to interpret it in a way that is relevant for the East-European context, and then to distill some of its major theological ideas regarding human dignity.